Nutritional profile of commercial infant and toddler food products available in Klang Valley/ Nadhirah Abd Razak and Naleena Devi Muniandy - Abd Razak, Nadhirah; Muniandy, Naleena Devi (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Many mothers provided commercial baby food products to their children, but studies showed that most of these products contained high sugar and sodium content. This had been overlooked by researchers, especially in Malaysia since not many studies were conducted in this area. The aims of this study were to assess the types of commercial infant and toddler food products available in Klang Valley, then compare selected nutrients content between categories and age groups. Samples of products were collected from different types of shops available in 9 areas in Klang Valley. Information was obtained from product's packaging or manufacturer's websites. Result showed that there were four types of products which were cereal, cookies or snack, simple pureed food and mixed food. There were significant differences (p<0.005) for calorie, carbohydrate, protein, total fat, sugar, sodium, saturated fat and fiber between the product categories. Then, between age groups, there was significant difference for saturated fat in cereal, as well as fat, sugar, sodium and saturated fat for cookies or snack, and calorie, carbohydrate, protein, sugar, sodium and fiber for mixed food. In conclusion, within the categories, cookies or snack had the highest sugar and sodium content and within age groups, both nutrients were the highest in stage 2 and 4. These findings lead to concerns as cookies or snack was usually given to babies as between meal snack and early exposure to sugar and sodium, as early as in stage 2 (7 to 9 months), could lead to obesity and other diseases later in life. Thus, the government and health professionals should provide education to parents or caregivers on making healthier food product choices for their children.